If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -28 = -7 + 3(a + 6) Reorder the terms: -28 = -7 + 3(6 + a) -28 = -7 + (6 * 3 + a * 3) -28 = -7 + (18 + 3a) Combine like terms: -7 + 18 = 11 -28 = 11 + 3a Solving -28 = 11 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -28 + -3a = 11 + 3a + -3a Combine like terms: 3a + -3a = 0 -28 + -3a = 11 + 0 -28 + -3a = 11 Add '28' to each side of the equation. -28 + 28 + -3a = 11 + 28 Combine like terms: -28 + 28 = 0 0 + -3a = 11 + 28 -3a = 11 + 28 Combine like terms: 11 + 28 = 39 -3a = 39 Divide each side by '-3'. a = -13 Simplifying a = -13
| 9k+4-3=-16 | | 4x^3-10x^2+6x=0 | | (2x+3y-5)dx+(3x-y-2)dy=0 | | 18=-7r+3r | | X^2+25x-7500=0 | | 9k+4+3=-16 | | 3p^2-15-15=0 | | 8v+2-5v=-29 | | 24-n/3=6 | | 2x+3+3x-17=180 | | 10x+5y+8z-5x+5z-9y= | | z+4=10 | | 3(4b+8)= | | 6x+4x=22.5 | | 5x+6x=22.5 | | 4x+5x=22.5 | | y=0.0124x+0.1568 | | 8+9+5z=-3+2z+7 | | x-(x+3)=4 | | x=3x+22 | | x-6+3x+8+2x+10=54 | | f(-1)=3+5 | | -3x-22+2x-6=4x-2 | | Y+8y=3 | | (-5x)+(-7x)=180 | | 2(4x+8)+2(6x+2)=60 | | 2x+12+4x-5+3x+2= | | 8cos^2x-5=1 | | 2x+3+x+6=42 | | (2x+12)+(4x-5)+(3x+2)= | | 3(15x-9y)+5(4y-x)= | | -4=c |